Contemporary Accounting - Bazley, Mike and Hancock, Phil (Australia Cengage Learning, 2004)
This brand new edition provides students with a thorough, systematic introduction to accounting principles and modern accounting issues and practices. Updated to reflect Australia's adoption of the International Reporting Standards.
Include Index, Appendix and Glossary
Keywords: Accounting -- Australia -- Accounting--Study and teaching (Higher)